The Microtubule Cytoskeleton during the Early Drosophila Spermiogenesis - Maria Giovanna Riparbelli; Veronica Persico; Giuliano Callaini (Cells, 2020)
Sperm elongation and nuclear shaping in Drosophila largely depends on the microtubule cytoskeleton that in early spermatids has centrosomal and non-centrosomal origins. We report here an additional γ-tubulin focus localized on the anterior pole of the nucleus in correspondence of the apical end of the perinuclear microtubules that run within the dense complex. The perinuclear microtubules are nucleated by the pericentriolar material, or centriole adjunct, that surrounds the basal body and are retained to play a major role in nuclear shaping. However, we found that both the perinuclear microtubules and the dense complex are present in spermatids lacking centrioles. Therefore, the basal body or the centriole adjunct seem to be dispensable for the organization and assembly of these structures. These observations shed light on a novel localization of γ-tubulin and open a new scenario on the distribution of the microtubules and the organization of the dense complex during early Drosophila spermiogenesis.